Neighborhood sustainability in urban renewal: An assessment framework. Issue 5 (September 2017) - Zheng, Helen W; Shen, Geoffrey QP; Song, Yan; Sun, Bingxia; Hong, Jingke
Urban renewal provides valuable opportunities for sustainable development. Sustainability assessment is considered a useful tool in ensuring sustainable development in practice. Although a number of studies have been conducted to evaluate the potential of urban renewal, studies on sustainability assessment in urban renewal at a neighborhood scale are often ignored. However, urban renewal is normally accompanied by many social, economic, and environmental conflicts among various stakeholders. The present paper proposes a framework for assessing neighborhood sustainability to support urban renewal decision making in high-density cities such as Hong Kong. This framework includes two components: (1) sustainability and building condition and (2) a decision-making matrix for urban renewal strategies. A case study was conducted to illustrate how this framework can be applied in the decision-making process of urban renewal projects. The results are expected to provide references for urban renewal decision making in high-density cities.